IMPACT OF THINNING AND FOLIAR-BORON-ZINC SPRAY ON SOME MORPHOLOGICAL AND PHYSIOLOGICAL INDICATORS IN APPLE TREE (MALUS DOMESTICA CV. GOLDEN DELICIOUS)-"TARTOUS GOVERNORATE" - Amali Abdo Al-Ahmad,; Muhammad Batha,; Bayan Muzhar, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The research was conducted in Tartous governorate on apple trees cv. Golden Delicious grafted on the rootstock “Malus domestica Borkh”, during two seasons 2019-2020 to study the impact of manual and chemical thinning using foliar boron /zinc spray separately or in combination on some morphological and physiological indicators. The results showed a significant increase in leaf area and its content of total chlorophyll and carotenoids in the second season (low fruit load) compared to the first season (heavy load) due to a rise in vegetative growth and a reduction in fruiting. During the heavy load season, a balance between vegetative and fruiting growth was noted when the manual and chemical thinning applied with no significant differences was found between the two seasons in leaf area, total chlorophyll and carotenoids content. On the other hand, the application of manual thinning, chemical thinning and foliar spraying with boron and zinc separately or together pointed out an increase in the branches content of carbohydrates and nitrogen and C/N ratio in the low load season compared to the control. Consequently, fruit thinning was more effective to obtain a balance between the seasons in term of leaf area, its pigments content, and C/N ratio in branches, which in turn mitigate the alternate bearing phenomenon.